A simple guide to ultrasound screening for placenta accreta spectrum for improving detection and optimizing management in resource limited settings. Issue 3 (18th August 2022) - Adu‐Bredu, Theophilus K.; Rijken, Marcus J.; Nieto‐Calvache, Albaro Jose; Stefanovic, Vedran; Aryananda, Rozi Aditya; Fox, Karin Anneliese; Collins, Sally L.; ,
Abstract : Placenta accreta spectrum is a pregnancy complication associated with severe morbidity and maternal mortality especially when not suspected antenatally and appropriate management instigated. Women in resource‐limited settings are more likely to face adverse outcomes due to logistic, technical, and resource inadequacies. Accurate prenatal imaging is an important step in ensuring good outcomes because it allows adequate preparation and an appropriate management approach. This article provides a simple three‐step approach aimed at guiding clinicians and sonographers with minimal experience in placental accreta spectrum through risk stratification and basic prenatal screening for this condition both with and without Doppler ultrasound.